Low Back Pain and Associated Factors among Hairdressers in Northern Ethiopia: A Cross-Sectional Study - Gebrerufael Solomon Tsegay; Berihu Fisseha Gebremeskel; Selam Desalegn Gezahegn; Desalegn Massa Teklemichael (Pain Research and Management)
Low back pain is one of the major occupational health problems ranked the highest in terms of years lived with disability, and it has an economic burden on individuals and society in general. Hairdressers are high-risk professionals, but they are usually getting less attention in research and policy actions. The objective of this study is to assess the magnitude and associated factors of low back pain among hairdressers working in female beauty salons of Mekelle, Northern Ethiopia. A cross-sectional study was employed from January up to March 2018. A simple random sampling was applied to select 344 participants. Interviewer-administered, pretested, and structured questionnaire was used. Bivariate and multivariate binary logistic regression analyses were performed using SPSS version 23. A p value of <0.05 was used to declare statistical significance. A total of 314 hairdressers participated, with a 91.3% response rate. The study found that the prevalence of low back pain was 47.5% with 95% CI (41.8–53.1). Marital status (AOR: 0.40, 95% CI (0.23–0.71)), awkward posture (AOR: 2.59, 95%CI (1.45–4.63)), working greater than 4 days in a week (AOR: 5.12, 95% CI (1.94–13.70)), the task of washing the client’s hair (AOR: 4.45, 95% CI (1.93–10.26)), having adjustable washing basin (AOR: 0.35, 95% CI (0.18–0.69)), job stress (AOR: 0.45, 95% CI (0.27–0.77)), and job satisfaction (AOR: 0.58, 95% CI (0.34–0.98)) were factors that show a statistically significant association with low back pain. This study found that low back pain is a major health problem among hairdressers. Marital status, awkward postures, working days per week, the task of washing the client’s hair, adjustable washing basin, job stress, and job satisfaction show a strong association with low back pain. The result suggests that effective intervention strategies for low back pain need to include ergonomic improvements and psychosocial and behavioral aspects of the participants.